Ethics of love and ethics of desire in the poetry of Cesar Moro - Vich, Víctor (2017)
What is love for Moro? What is desire? What causes them? What effects do they have in subjectivity? I intend to study the dynamics of love and desire in the poetry of Cesar Moro using three types of images: as events leading to a process of truth, as forces suspending traditional moral and as signs of something that goes beyond to the subjectivity and depart from any rational logic.